Sudden Stops and Optimal Policy in a Two-agent Economy - Biljanovska, Nina (IMF Working Papers; Working Paper ;, 2022)
We introduce heterogeneity in terms of workers and entrepreneurs in an otherwise standard Fisherian model to study Sudden Stop dynamics and optimal policy. We show that the distinction between workers and entrepreneurs introduces a distributive externality that is absent from the representative-agent setup. While in tranquil times redistribution is driven by the relative marginal utilities of consumption, the planner additionally favors entrepreneurs during Sudden Stops to mitigate Fisherian deation. Although agentheterogeneity does not add much in explaining the Sudden Stop phenomena, it adds to the understanding of how policies can best be designed to alleviate the negative effects of Sudden Stops.